Phosphogypsum-based adsorbing material as well as preparation method and application thereof
Through the preparation method of phosphogypsum-based adsorption materials, the reaction of ammonium chloride solution and ammonia water, combined with CO2 and modification treatment, the problem of low resource utilization efficiency of phosphogypsum is solved, and high-efficiency fluoride ion adsorption and calcium fluoride recovery is achieved. , improving the utilization rate and environmental protection of phosphogypsum resources.
Patent Information
- Application Number
- CN202411395702.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2024-12-27
AI Technical Summary
The existing technology has low utilization efficiency, poor economic benefits and high environmental risks in the resource utilization of phosphogypsum, which is difficult to meet the needs of comprehensive utilization of phosphogypsum resources, resulting in environmental pollution and resource waste.
The preparation method of phosphogypsum-based adsorbent material is adopted, and the phosphogypsum-based adsorbent material is prepared by leaching reaction of ammonium chloride solution, ammonia water and CO2 reaction, slurry adjustment and modification treatment, and combined with PP cotton plates to prepare phosphogypsum-based adsorbent material to achieve efficient utilization of calcium sulfate and fluoride ions. efficient adsorption.
The utilization rate of phosphogypsum resources has been improved, efficient adsorption of fluoride ions and recycling of calcium fluoride, reduced production costs, reduced energy consumption and equipment investment, and formed an environmentally friendly and efficient phosphogypsum resource recycling process.
Smart Images

Figure CN119186482A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of phosphogypsum recovery, and in particular to a phosphogypsum-based adsorption material and a preparation method and application thereof. Background Art
[0002] Since phosphogypsum contains complex impurities such as phosphorus, fluorine, ammonium nitrogen, and even heavy metals, its resource utilization is difficult, and the current treatment method is mainly waste storage. However, waste storage not only occupies a large amount of land, consumes maintenance funds, and has the risk of dam collapse, but also produces leachate with low pH value, strong corrosiveness, and high total phosphorus concentration after being washed and leached by rainwater. Soluble phosphorus, ammonia nitrogen, fluorine and other impurities in the leachate are easy to migrate to the surrounding soil, water bodies, and atmospheric environment, which can easily cause environmental pollution and threaten the health of surrounding residents. Therefore, the resource utilization of phosphogypsum is directly related to the sustainable development of the phosphorus chemical industry and the protection of the ecological environment, and is of great necessity and urgency.
[0003] At present, domestic and foreign scholars use phosphogypsum to prepare calcium carbonate materials, mainly through the following two processes: (1) using phosphogypsum as raw material to prepare calcium carbonate by direct method; (2) using indirect method, first leaching and separating calcium ions in phosphogypsum, and then using the calcium ion-rich leachate as raw material to prepare calcium carbonate. However, the scheme of converting phosphogypsum into calcium carbonate has problems such as low utilization efficiency, poor economic benefits, and high environmental risks in actual industrial production. It is difficult to meet the demand for the utilization of phosphogypsum resources, which seriously restricts the improvement of the comprehensive utilization level of resources.
[0004] Therefore, it is necessary to provide a solution to improve the utilization rate of phosphogypsum resources. Summary of the invention
[0005] In view of this, the present application provides a phosphogypsum-based adsorption material and a preparation method and application thereof, to solve the problem of how to improve the utilization rate of phosphogypsum resources.
[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions: In a first aspect, the present application provides a method for preparing a phosphogypsum-based adsorption material, comprising the following steps: S1. adding phosphogypsum to an ammonium chloride solution to carry out a leaching reaction, and filtering to obtain a first filtrate and a first filter residue; S2. Ammonia and a dispersant were added to the first filtrate, and CO2 was introduced into the reaction and filtered to obtain a second filtrate and a second residue; S3. The second filter residue is slurried, and then a modifier is added to obtain a modified slurry; S4. The modified slurry is heated and a PP cotton board is added, and after ultrasonic treatment, the slurry is dried to obtain a phosphogypsum-based adsorption material.
[0007] Preferably, the method further comprises recycling the second filtrate in step S2 to the leaching reaction in step S1.
[0008] Preferably, in step S1, the concentration of the ammonium chloride solution is 2-4 mol / L, the solid-liquid ratio of phosphogypsum to the ammonium chloride solution is 6-10 mL / g, and the leaching reaction temperature is 40-80°C.
[0009] Preferably, in step S2, the molar ratio of ammonia in the ammonia water to calcium in the first filtrate is 1.5-2.4:1, the amount of dispersant used is 2-6% of the mass of phosphogypsum; the CO2 introduction rate is 50-120 mL / min, and the CO2 reaction temperature is 30-50°C.
[0010] Preferably, the dispersant includes one or more of polyethylene glycol 400, polyethylene glycol 800, polyethylene glycol 2000, P123, sodium dodecylbenzene sulfonate, and sodium dodecyl sulfate.
[0011] Preferably, in step S3, the modifier includes at least one of sodium stearate, triisostearoyl isopropyl titanate, distearoyloxyisopropyl aluminate, and DL-411; and the amount of the modifier is 0.4-1.2% of the mass of the second filter residue.
[0012] Preferably, in step S4, the heating temperature of the modified slurry is 25-65°C.
[0013] In a second aspect, the present application provides a phosphogypsum-based adsorption material.
[0014] In a third aspect, the present application provides an application of phosphogypsum-based adsorption material in treating fluoride-containing wastewater.
[0015] Preferably, the application method is: putting the phosphogypsum-based adsorption material into fluorine-containing wastewater and letting it stand, taking it out and drying it to obtain a PP cotton board with calcium fluoride attached, knocking the PP cotton board with calcium fluoride attached to make the calcium fluoride fall off, and then recovering the PP cotton board.
[0016] The beneficial effects of this application are as follows: The present invention can realize the efficient utilization of calcium sulfate, the main component of phosphogypsum; and the present invention is based on the organic combination of phase transfer method and calcium carbonate dispersion and modification technology, and can realize the efficient preparation of fluoride ion adsorption materials, that is, it can make resource utilization of consumed and idle stockpiled phosphogypsum, and can realize the efficient adsorption of fluoride ions and obtain calcium fluoride products with higher added value.
[0017] The present invention uses PP cotton board as a carrier to prepare the phosphogypsum-based adsorption material, which is used to adsorb fluoride ions and can achieve "filter element-like" operation. The adsorption material can be replaced regularly according to the concentration of fluoride ions in the liquid to be treated and the treated water conditions. Compared with traditional adsorption materials, the present invention does not require multiple filter presses when replacing the adsorption material, thereby reducing energy consumption and equipment investment. It only needs to take out the adsorption material from the liquid to be treated and replace it with a new adsorption material.
[0018] After the phosphogypsum-based adsorption material of the present invention has adsorbed fluoride ions, it only needs to be dried and then beaten. On the one hand, the PP cotton board can be quickly recovered for re-preparing the adsorption material. On the other hand, the adsorption product calcium fluoride can be recycled, which can further reduce the production cost of the process.
[0019] The invention has cheap raw materials, simple required equipment and low production cost, thus forming an environmentally friendly and efficient process for recycling phosphogypsum resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The XRD pattern of the calcium carbonate product prepared in Example 1; Figure 2 This is the XRD pattern of the solid material obtained after adsorption in Example 6; Figure 3 The XRD pattern of the calcium carbonate product prepared in Example 2; Figure 4 This is the XRD pattern of the solid material obtained after adsorption in Example 7; Figure 5 The XRD pattern of the calcium carbonate product prepared in Example 3; Figure 6 This is the XRD pattern of the solid material obtained after adsorption in Example 8; Figure 7 The XRD pattern of the calcium carbonate product prepared in Example 4; Figure 8 is the XRD pattern of the solid material obtained after adsorption in Example 9; Fig. 9 The XRD pattern of the calcium carbonate product prepared in Example 5; Fig.10 is the XRD pattern of the solid material obtained after adsorption in Example 10; Fig.11 This is a process flow chart of this application. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0022] The present application provides a method for preparing a phosphogypsum-based adsorption material, comprising the following steps: S1. adding phosphogypsum to an ammonium chloride solution to carry out a leaching reaction, and filtering to obtain a first filtrate and a first filter residue; S2. Ammonia and a dispersant were added to the first filtrate, and CO2 was introduced into the reaction and filtered to obtain a second filtrate and a second residue; S3. The second filter residue is slurried, and then a modifier is added to obtain a modified slurry; S4. The modified slurry is heated and a PP cotton board is added, and after ultrasonic treatment, the slurry is dried to obtain a phosphogypsum-based adsorption material.
[0023] In step S1 of the present application, phosphogypsum and ammonium chloride are phase-transferred and leached to obtain a first filtrate, which is a calcium-containing solution. In step S2, a dispersant is added to the calcium-containing solution, and CO2 is introduced under ammonia conditions. This can make full use of calcium sulfate, the main component of phosphogypsum, to prepare a high-purity calcium carbonate product, i.e., the second filter residue. On the one hand, this can achieve the absorption of carbon dioxide. On the other hand, due to the use of the dispersant, the calcium carbonate can be effectively dispersed, thereby improving the viscosity, fluidity and precipitation resistance of the material, making it suitable for use in various applications.
[0024] In some embodiments, the second filtrate in step S2 is further recycled to the leaching reaction in step S1.
[0025] In step S1, the concentration of ammonium chloride solution is 2-4 mol / L, the solid-liquid ratio of phosphogypsum to ammonium chloride solution is 6-10 mL / g, and the leaching reaction temperature is 40-80 ° C. Here, the reaction of phosphogypsum with NH4Cl solution is a phase transfer reaction, that is, transferring elements in the solid phase to the liquid phase. The transfer efficiency of calcium ions is expressed by the leaching rate (the same below), as an indicator of the transfer process. If the liquid-solid ratio is too low, the leaching rate of calcium ions is low. If the liquid-solid ratio is too high, more NH4Cl is required. At the same time, the concentration of calcium ions in the leachate is reduced, which increases the cost and difficulty of subsequent drying. If the temperature is too low, the reaction rate is reduced, and the calcium ion leaching rate is reduced. If it is necessary to achieve the expected leachate at a lower temperature, the reaction time will be greatly increased, which is not conducive to improving efficiency. If the temperature is too high, the energy consumption increases, and the evaporation amount also increases, which is not conducive to energy consumption control, nor to subsequent water balance management.
[0026] In step S2, the molar ratio of ammonia in the ammonia water to calcium in the first filtrate is 1.5-2.4:1, and the amount of the dispersant is 2-6% of the mass of the phosphogypsum; the CO2 introduction rate is 50-120 mL / min, and the CO2 reaction temperature is 30-50°C.
[0027] Dispersants include one or more of polyethylene glycol 400, polyethylene glycol 800, and polyethylene glycol 2000. The function of the dispersant is to prevent serious agglomeration of calcium carbonate during precipitation. If the agglomeration phenomenon is not controlled during the preparation process, the subsequent modification and dispersion on the PP cotton will not be uniform, making it difficult to control the product quality. The mechanism of the dispersant is: Ca 2+ It can interact with the hydroxyl groups in polyhydroxy compounds through electrostatic matching, thereby reducing the activation energy of nucleation of calcium carbonate crystals and accelerating the nucleation rate. In the early stage of calcium carbonate crystal nucleation, adding a small amount of polyhydroxy dispersant can accelerate its nucleation rate and reduce the surface energy of the crystal nucleus, so that smaller calcium carbonate nuclei can exist stably, and finally form calcium carbonate particles with good dispersion and uniform particle size.
[0028] In step S3, the modifier includes at least one of sodium stearate, triisostearoyl titanate isopropyl, distearoyloxy isopropyl aluminate, and DL-411; the amount of the modifier is 0.4-1.2% of the mass of the second filter residue; the modifier can make the prepared calcium carbonate evenly dispersed in the PP cotton board under the action of ultrasound; the slurry concentration is 160-200g / 100cm 3 .
[0029] In step S4, the heating temperature of the modified slurry is 25-65°C.
[0030] Specifically, the preparation method of the phosphogypsum-based adsorption material comprises the following steps: The phosphogypsum is leached with NH4Cl solution, and the leaching solution and filter residue are obtained after filtration. The reaction equation is shown in formula (1). The leaching solution is mainly rich in Ca 2+ and NH 4+ Plasma, the reaction mechanism is: calcium sulfate in phosphogypsum is slightly soluble in water. When strong electrolyte solutions such as ammonium chloride are added to the phosphogypsum suspension, according to the "salt effect", the total concentration of ions in the solution increases, the mutual attraction between ions increases, and the chance of calcium ions dissociated from calcium sulfate combining with sulfate ions to form molecules decreases, and then the amount of calcium sulfate in the system gradually decreases, and calcium sulfate gradually dissolves into calcium ions and sulfate ions.
[0031] Phosphogypsum(s) + NH4Cl(aq)——Ca 2+ (aq) + SO4 2- (aq) + NH 4+ (aq) + Cl - (aq) +SiO2(s), formula (1).
[0032] Ammonia water and dispersant are added to the leachate, and CO2 is introduced under stirring conditions. After the reaction is completed, the reaction liquid is filtered, and the filter residue is dried to obtain calcium carbonate. The filtrate is reused in the previous step to leach phosphogypsum. At this time, in the medium of ammonia water, the leachate is used as a raw material, and the CO2 reaction process involves a gas-liquid-solid three-phase chemical reaction, which is mainly divided into four stages: 1) ammonia water absorbs CO2; 2) ammonium carbonate ((NH4)2CO3) or ammonium bicarbonate (NH4HCO3) is generated; 3) (NH4)2CO3 or NH4HCO3 reacts with Ca 2+ Reaction; 4) CaCO3 precipitation is generated. The relevant reaction equations are shown in equations (2)-(9).
[0033]
[0034] Next, the obtained calcium carbonate is slurried and a modifier is added. The slurry is heated and fully stirred for a period of time, and then a PP cotton board is added. After ultrasonic dispersion, the slurry is taken out and dried to obtain a phosphogypsum-based high-efficiency fluoride ion adsorption material. The present invention adopts sodium stearate, triisostearoyl isopropyl titanate, distearyloxy isopropyl aluminate, DL-411 and other modifiers to wet-modify the calcium carbonate material obtained in step 2, which can form a uniform and stable oleophilic and hydrophobic coating layer, significantly improve the hydrophobicity and dispersibility of light calcium carbonate, on the one hand, can improve its dispersion uniformity and stability on the PP cotton board, on the other hand, can enhance the heat resistance, strength and rigidity of the PP cotton board products.
[0035] The present application provides a phosphogypsum-based adsorption material.
[0036] The present application provides an application of a phosphogypsum-based adsorption material in treating fluoride-containing wastewater.
[0037] This application is based on the organic combination of phase transfer method and calcium carbonate dispersion and modification technology, which can realize the rapid preparation of phosphogypsum-based high-efficiency fluoride ion adsorption materials. At the same time, using PP cotton board as a carrier, it can realize the efficient separation of adsorption products and the reuse of the carrier.
[0038] The application method of phosphogypsum-based adsorption material for adsorbing fluoride-containing wastewater is as follows: putting the phosphogypsum-based adsorption material into the fluoride-containing wastewater and letting it stand, taking it out and drying it to obtain a PP cotton board with calcium fluoride attached, knocking the PP cotton board with calcium fluoride attached to make the calcium fluoride fall off, and then recovering the PP cotton board.
[0039] Since Ksp of calcium carbonate is 2.8×10 -9 , while Ksp of calcium fluoride is 2.7×10 -11, the phosphogypsum-based high-efficiency fluoride ion adsorption material will generate calcium fluoride products after reacting with fluoride ions. When the calcium carbonate dispersed in the PP cotton board is completely converted into calcium fluoride, the high-purity calcium fluoride and the PP cotton board can be separated by simple drying and beating. The high-purity calcium fluoride is recovered and sold as a product, and the PP cotton board is reused. In addition, due to the K of calcium fluoride SP Significantly lower than the K of calcium carbonate SP value, so calcium carbonate can react with fluoride ions in the solution to obtain calcium fluoride under acidic or alkaline conditions, thereby achieving the removal of fluoride ions in wastewater.
[0040] The present solution is further described below through specific embodiments.
[0041] Source of raw materials: In Examples 1-3 of the present application, phosphogypsum was collected from a phosphorus chemical enterprise in Hubei, and the contents of its main components were: SiO2: 4.13%, CaO: 30.08%, SO3: 39.53%, Al2O3: 0.59%, MgO: 0.11%; In Examples 4-5 of the present application, phosphogypsum was collected from a phosphorus chemical enterprise in Guizhou, and the contents of its main components were: SiO2: 2.13%, CaO3: 2.18%, SO3: 37.59%, Al2O3: 0.29%, MgO: 0.15%.
[0042] Example 1 A method for preparing a phosphogypsum-based adsorption material comprises the following steps: S1. adding phosphogypsum to 2 mol / L ammonium chloride solution with a solid-liquid ratio of 6 mL / g, stirring at 40°C for 120 min for leaching reaction, and filtering to obtain a first filtrate and a first filter residue; S2. Ammonia water and dispersant polyethylene glycol 400 were added to the first filtrate, the molar ratio of ammonia in the ammonia water to calcium in the first filtrate was 1.5:1, the amount of dispersant was 2% of the mass of phosphogypsum, and CO2 was introduced at 120 mL / min under stirring conditions, and the reaction was carried out at 30°C for 45 minutes, and then filtered to obtain a second filtrate and a second filter residue. The second filter residue was dried to obtain a calcium carbonate product. XRD analysis showed Figure 1 The second filtrate is recycled to the leaching reaction of step S1 to leach phosphogypsum; S3. The second filter residue is 160g / 100cm 3 The slurry was adjusted, and then sodium stearate was added for modification, with the amount of sodium stearate being 1.2% of the mass of calcium carbonate to obtain a modified slurry; S4. After the modified slurry is stirred at 65°C for 30 minutes, a PP cotton board is added, and after ultrasonic dispersion for 40 minutes, the slurry is taken out and air-dried to obtain the phosphogypsum-based adsorption material.
[0043] Example 2 A method for preparing a phosphogypsum-based adsorption material comprises the following steps: S1. adding phosphogypsum to 4 mol / L ammonium chloride solution with a solid-liquid ratio of 10 mL / g, stirring at 80°C for 60 min for leaching reaction, and filtering to obtain a first filtrate and a first filter residue; S2. Ammonia water and dispersant polyethylene glycol 800 were added to the first filtrate, the molar ratio of ammonia in the ammonia water to calcium in the first filtrate was 2:1, the amount of dispersant was 6% of the mass of phosphogypsum, and CO2 was introduced at 50 mL / min under stirring conditions, and the reaction was carried out at 30°C for 80 minutes, and then filtered to obtain a second filtrate and a second filter residue. The second filter residue was dried to obtain a calcium carbonate product. XRD analysis showed Figure 3 The second filtrate is recycled to the leaching reaction of step S1 to leach phosphogypsum; S3. The second filter residue is 200g / 100cm 3 The slurry is prepared, and then triisostearoyl titanate isopropyl is added for modification, wherein the amount of triisostearoyl titanate isopropyl is 0.4% of the mass of calcium carbonate to obtain a modified slurry; S4. After the modified slurry was stirred at 25°C for 120 minutes, a PP cotton board was added, and after ultrasonic dispersion for 40 minutes, the slurry was taken out and dried to obtain the phosphogypsum-based adsorption material.
[0044] Example 3 A method for preparing a phosphogypsum-based adsorption material comprises the following steps: S1. adding phosphogypsum to 5 mol / L ammonium chloride solution with a solid-liquid ratio of 8 mL / g, stirring at 80°C for 60 min for leaching reaction, and filtering to obtain a first filtrate and a first filter residue; S2. Ammonia water and dispersant polyethylene glycol 200 were added to the first filtrate, the molar ratio of ammonia in the ammonia water to calcium in the first filtrate was 2.4:1, the amount of dispersant was 3% of the mass of phosphogypsum, and CO2 was introduced at 80 mL / min under stirring conditions, and the reaction was carried out at 40°C for 80 minutes, and then filtered to obtain a second filtrate and a second filter residue. The second filter residue was dried to obtain a calcium carbonate product. XRD analysis showed Figure 5 The second filtrate is recycled to the leaching reaction of step S1 to leach phosphogypsum; S3. The second filter residue is 200g / 100cm 3 The slurry is adjusted, and then sodium stearate is added for modification, wherein the amount of sodium stearate is 0.8% of the mass of calcium carbonate to obtain a modified slurry; S4. After the modified slurry was stirred at 35°C for 80 minutes, a PP cotton board was added, and after ultrasonic dispersion for 60 minutes, the slurry was taken out and dried to obtain the phosphogypsum-based adsorption material.
[0045] Example 4 A method for preparing a phosphogypsum-based adsorption material comprises the following steps: S1. adding phosphogypsum to 3 mol / L ammonium chloride solution with a solid-liquid ratio of 8 mL / g, stirring at 40°C for 120 min for leaching reaction, and filtering to obtain a first filtrate and a first filter residue; S2. Ammonia water and dispersant polyethylene glycol 800 were added to the first filtrate, the molar ratio of ammonia in the ammonia water to calcium in the first filtrate was 1.5:1, the amount of dispersant was 3% of the mass of phosphogypsum, and CO2 was introduced at 80 mL / min under stirring conditions, and the reaction was carried out at 30°C for 60 minutes, and then filtered to obtain a second filtrate and a second filter residue. The second filter residue was dried to obtain a calcium carbonate product. XRD analysis showed Figure 7 The second filtrate is recycled to the leaching reaction of step S1 to leach phosphogypsum; S3. The second filter residue is 160g / 100cm 3 The slurry is adjusted, and then sodium stearate is added for modification, wherein the amount of sodium stearate is 0.8% of the mass of calcium carbonate to obtain a modified slurry; S4. After the modified slurry is stirred at 65°C for 30 minutes, a PP cotton board is added, and after ultrasonic dispersion for 40 minutes, the slurry is taken out and air-dried to obtain the phosphogypsum-based adsorption material.
[0046] Example 5 A method for preparing a phosphogypsum-based adsorption material comprises the following steps: S1. adding phosphogypsum to 5 mol / L ammonium chloride solution with a solid-liquid ratio of 8 mL / g, stirring at 80°C for 60 min for leaching reaction, and filtering to obtain a first filtrate and a first filter residue; S2. Ammonia water and dispersant polyethylene glycol 200 were added to the first filtrate, the molar ratio of ammonia in the ammonia water to calcium in the first filtrate was 2.4:1, the amount of dispersant was 3% of the mass of phosphogypsum, and CO2 was introduced at 80 mL / min under stirring conditions, and the reaction was carried out at 40°C for 80 minutes, and then filtered to obtain a second filtrate and a second filter residue. The second filter residue was dried to obtain a calcium carbonate product. XRD analysis showed Fig. 9 The second filtrate is recycled to the leaching reaction of step S1 to leach phosphogypsum; S3. The second filter residue is 200g / 100cm 3 The slurry is adjusted, and then sodium stearate is added for modification, wherein the amount of sodium stearate is 0.8% of the mass of calcium carbonate to obtain a modified slurry; S4. After the modified slurry is stirred at 80°C for 30 minutes, a PP cotton board is added, and after ultrasonic dispersion for 60 minutes, the slurry is taken out and air-dried to obtain the phosphogypsum-based adsorption material.
[0047] Example 6 An application method of a phosphogypsum-based adsorption material: the phosphogypsum-based adsorption material obtained in Example 1 is placed in fluorine-containing wastewater with a pH value of 4 and a fluorine ion concentration of 500 mg / L, and the adsorption material is taken out after adsorption for 4 hours. The adsorbed phosphogypsum-based high-efficiency fluorine ion adsorption material is dried at 80° C. for 60 minutes, and then knocked to make the solid matter on the adsorption material fall off and be collected. The XRD analysis of the fallen and collected solid matter shows Figure 2 , PP cotton board is recycled.
[0048] Example 7 An application method of a phosphogypsum-based adsorption material: the phosphogypsum-based adsorption material obtained in Example 2 is placed in fluorine-containing wastewater with a pH value of 3 and a fluorine ion concentration of 500 mg / L, and the adsorption material is taken out after adsorption for 5 hours. The adsorbed phosphogypsum-based high-efficiency fluorine ion adsorption material is dried at 60° C. for 180 minutes, and then tapped to make the solid matter on the adsorption material fall off and be collected. The XRD analysis of the fallen and collected solid matter shows Figure 4 , PP cotton board is recycled.
[0049] Example 8 An application method of a phosphogypsum-based adsorption material: the phosphogypsum-based adsorption material obtained in Example 3 is placed in fluorine-containing wastewater with a pH value of 3 and a fluorine ion concentration of 500 mg / L, and the adsorption material is taken out after adsorption for 5 hours. The adsorbed phosphogypsum-based high-efficiency fluorine ion adsorption material is dried at 70°C for 120 minutes, and then knocked to make the solid matter on the adsorption material fall off and collect it. The XRD analysis of the solid matter that fell off and collected shows Figure 6 , PP cotton board is recycled.
[0050] Example 9 An application method of a phosphogypsum-based adsorption material: the phosphogypsum-based adsorption material obtained in Example 4 is placed in fluorine-containing wastewater with a pH value of 4 and a fluorine ion concentration of 500 mg / L, and the adsorption material is taken out after adsorption for 4 hours. The adsorbed phosphogypsum-based high-efficiency fluorine ion adsorption material is dried at 80° C. for 60 minutes, and then knocked to make the solid matter on the adsorption material fall off and be collected. The XRD analysis of the fallen and collected solid matter shows Figure 8 , PP cotton board is recycled.
[0051] Example 10 An application method of a phosphogypsum-based adsorption material: the phosphogypsum-based adsorption material obtained in Example 5 is placed in fluorine-containing wastewater with a pH value of 3 and a fluorine ion concentration of 500 mg / L, and the adsorption material is taken out after adsorption for 4 hours. The adsorbed phosphogypsum-based high-efficiency fluorine ion adsorption material is dried at 70°C for 120 minutes, and then knocked to make the solid matter on the adsorption material fall off and collect it. The XRD analysis of the solid matter that fell off and collected shows Fig.10 , PP cotton board is recycled.
[0052] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for preparing a phosphogypsum-based adsorption material, characterized in that: The following steps are involved: S1. adding phosphogypsum to an ammonium chloride solution to carry out a leaching reaction, and filtering to obtain a first filtrate and a first filter residue; S2. Ammonia and a dispersant are added to the first filtrate, and CO2 is introduced into the reaction and filtered to obtain a second filtrate and a second residue; S3. The second residue is slurried, and then a modifier is added to obtain a modified slurry; S4. The modified slurry is heated and a PP cotton board is added, and after ultrasonic treatment, the phosphogypsum-based adsorption material is obtained by air-drying.
2. The method for preparing the phosphogypsum-based adsorption material according to claim 1, characterized in that: The method further includes recycling the second filtrate in step S2 to the leaching reaction in step S1.
3. The method for preparing the phosphogypsum-based adsorption material according to claim 1, characterized in that: In step S1, the concentration of the ammonium chloride solution is 2-4 mol / L, the solid-liquid ratio of phosphogypsum to the ammonium chloride solution is 6-10 mL / g, and the leaching reaction temperature is 40-80°C.
4. The method for preparing the phosphogypsum-based adsorption material according to claim 1, characterized in that: In step S2, the molar ratio of ammonia in the ammonia water to calcium in the first filtrate is 1.5-2.4:1, the amount of the dispersant is 2-6% of the mass of the phosphogypsum; the CO2 introduction rate is 50-120 mL / min, and the CO2 reaction temperature is 30-50°C.
5. The method for preparing the phosphogypsum-based adsorption material according to claim 1, characterized in that: The dispersant includes one or more of polyethylene glycol 400, polyethylene glycol 800, and polyethylene glycol 2000.
6. The method for preparing the phosphogypsum-based adsorption material according to claim 1, characterized in that: In step S3, the modifier includes at least one of sodium stearate, triisostearoyl isopropyl titanate, distearoyloxyisopropyl aluminate, and DL-411; and the amount of the modifier used is 0.4-1.2% of the mass of the second filter residue.
7. The method for preparing phosphogypsum-based adsorption material according to claim 1, characterized in that: In step S4, the heating temperature of the modified slurry is 25-65°C.
8. A phosphogypsum-based adsorption material obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the phosphogypsum-based adsorption material as claimed in claim 8 in treating fluoride-containing wastewater.
10. A use according to claim 9, characterized in that The application method is as follows: putting the phosphogypsum-based adsorption material into fluorine-containing wastewater and letting it stand, taking it out and drying it to obtain a PP cotton board with calcium fluoride attached, knocking the PP cotton board with calcium fluoride attached to make the calcium fluoride fall off, and then recovering the PP cotton board.
